Information Retrieval: A Communication Process in the 21st Century Library - Umeozor, Susan Nnadozie (International Journal of Knowledge Content Development & Technology, 2020)
Communication is a process involving a group of interrelated elements working together for the purpose of information transfer. This paper discusses information retrieval as a communication process in the 21st century library. The difficulties associated with access to recorded knowledge through bibliographic control devices have been exacerbated by the interposition of additional encoding processes in the library and further decoding by the users. In addition, the innovation of internet/web has revolutionized the means and mode of communication process in the library by flooding information seekers with information and creating an illusion of self-sufficiency in many users. This notwithstanding, reference services have remained vital aspects of the library and information profession because it is still the librarian’s job to provide researchers with expert assistance in locating the most useful information. Information and Communication Technology (ICT) has not relegated reference librarians to the background but has only changed their roles, activities, and their nomenclature and made their jobs more effective, user friendly and yet challenging. With these changes in information seeking behaviour and pattern, a cybernetic approach to information retrieval has emerged emphasizing adaptive control mechanisms and feedback processes. Librarians, as forebearers of refined information, should, through virtual reference services, assist information users find the needle in a haystack among a lot of information on the web. Counseling and retrieval process need to go together to assist users in cognitive and concept development because information retrieval in the library cannot be bereft of the counseling services from the librarians. Libraries should strive to continuously remain relevant by keeping abreast with changes in the behaviour of information users because digital reference service, as a supplement for the traditional reference service, has become a general term for contemporary librarians. URL: http://ijkcdt.net/xml/22689/22689.pdf